Retail diversity for dietary diversity: Resolving food-safety versus nutrition priorities in Hanoi - Raneri, Jessica Evelyn; Wertheim-Heck, Sigrid C.O. (2019)
Amid rapidly transforming urban food environments, Asia’s cities are faced with the dilemma of ensuring food and nutrition security for their populations while also combatting food-safety concerns. The current food environment in Hanoi, Viet Nam, only provides a minimal level of diet quality for the urban poor. Modernization policies aim to improve food safety by promoting the closure of open-air markets in favour of supermarkets and convenience stores. Traditional open-air markets are the urban population’s main source of food and ensure a healthy diet, but they do not offer formal food-safety guarantees. In contrast, modern retail outlets, such as supermarkets and convenience stores, provide foods with safety guarantees, but are not utilized by the urban poor for myriad reasons, including cultural shopping preferences, habits and convenience (hours of operation, formality, cost and perceived freshness). Though designed to increase the consumption of safe foods in Hanoi, these modern outlets may also stimulate the consumption of unhealthy ultra-processed foods and reinforce food-access inequality. The continued closure of traditional open-air markets in favour of modern retail outlets may be jeopardizing the future diet quality of Hanoi’s urban poor. We recommend that food-safety policies embrace the existing diversity of local food retail systems and identify opportunities to improve food safety at open-air fresh food markets.